Edukasi Melalui Flipbook Berbasis Digital Sebagai Upaya Pencegahan Resiko Penyalahgunaan Narkoba Pada Remaja: Digital Flipbook-Based Education as an Effort to Prevent the Risk of Drug Abuse Among Adolescents - Wati, Ni Made Nopita; Thrisna Dewi, Ni Luh Putu; Lisnawati, Ketut; Sanjiwani, A.A Sri Sanjiwani; Sudarma, Nyoman (Chakra Brahmanda Lentera Institute, 2025)
Drug abuse among adolescents continues to rise and poses a serious threat to the future of the younger generation. Existing educational efforts still rely heavily on conventional methods that are less appealing to today’s digital-native youth. Thus, an innovative and interactive educational medium is urgently needed. This community service project applied a participatory-educational approach and was conducted at a vocational health school in Bali. Participants included school counselors and students. Activities included situation analysis, development and validation of a digital flipbook, delivery of drug education using the flipbook, and evaluation of knowledge through pre- and post-tests. The use of digital flipbook significantly improved participants' knowledge. The proportion of students with good knowledge increased from 7.4% to 81.5%, while those with poor knowledge drastically decreased. Participants found the flipbook engaging and easy to use. The digital flipbook is an effective educational tool to enhance adolescent knowledge on drug abuse prevention. It is recommended for integration into school-based youth development and anti-drug programs.